Exploration of Biomarkers for Amoxicillin/Clavulanate‐Induced Liver Injury: Multi‐Omics Approaches. Issue 3 (26th October 2016) - Lee, J; Ji, SC; Kim, B; Yi, S; Shin, KH; Cho, JY; Lim, KS; Lee, SH; Yoon, SH; Chung, JY; Yu, KS; Park, HS; et al.
Abstract : To explore potential biomarkers for amoxicillin/clavulanate‐induced liver injury (AC‐DILI), we conducted a clinical trial in 32 healthy subjects based on multi‐omics approaches. Every subject was administered amoxicillin/clavulanate for 14 days. The liver‐specific microRNA‐122 (miR‐122) level increased prior to and correlated well with the observed alanine aminotransferase (ALT) level increase. This result indicates its potential as a sensitive early marker for AC‐DILI. We also identified urinary metabolites, such as azelaic acid and 7‐methylxanthine, with levels that significantly differed among the groups classified by ALT elevation level on day 8 after drug administration ( P < 0.05). Lymphocyte proliferation in response to the drug was also observed. These findings demonstrate sequential changes in the process of AC‐DILI, including metabolic changes, increased miR‐122 level, increased liver enzyme activity, and enhanced lymphocyte proliferation after drug administration. In conclusion, this study provides potential biomarkers for AC‐DILI based on currently known mechanisms using comprehensive multi‐omics approaches.